Effect of Pre-dispersing Metakaolin in Water on the Properties, Hydration, and Metakaolin Distribution in Mortar - Geng, Haining; Chen, Wei; Li, Qiu; Shui, Zhonghe; Yuan, Bo (Frontiers in Materials, 2019)
The effects of pre-dispersing metakaolin (MK) in water on the properties and hydration of mortar and distribution of MK particles in mortar were characterized by analytical techniques. Zeta-potential of MK-water dispersion significantly decreased with the increase of pH of solution, resulting in a stable dispersion at pH of 8 with zeta-potential of −40 mV. The bulk density of MK-water slurry rapidly increased with water/MK ratio due to the surface tension force of water and filling of spaces by water, resulting in a maximum bulk density of 665.2 kg/m3 at water/MK ratio of 1.0. Comparing to that of powder MK, pre-dispersing MK in water did not alter hydration products, slightly improved compressive strength, and pore structure, but further reduced shrinkage and significantly improved the uniformed distribution of MK particles in mortar.